PENGARUH KUALITAAS LAYANAN TERHADAP LOYALITAS KONSUMEN YANG DIMEDIASI OLEH NYAMAN COFFEE MATARAM - Ayu Khairunnisa; Junaidi Sagir; Rusminah, Rusminah (Yayasan Nusantara Hasana Berdikari, 2024)
The goals of this research is to determine the effect of E-Service Quality on E- Customer Loyalty by mediating E-Customer Satisfaction (Nyaman Coffee consumer study in Mataram). The population is all Shopee consumers in Mataram City, while the sample is 85 consumers using purposive sampling. This type of research is associative research. Processing data in this study using SPSS 23.0 for windows software. In which the validity test, reliability test, classical assumption test, analisys path test, significance test (t test), coefficient of determination test (R2), and sobel test were carried out. Based on the results of the analysis, all variables have a partial effect where E-Service Quality affects E-Customer Loyalty, E-Customer Satisfaction affects E-Customer Loyalty, E-Service Quality affects E-customer satisfaction. Based on these results, it is recommended that Shopee can improve the quality of E-Service Quality and increase customer satisfaction, resulting in increased customer loyalty to product purchases in the Nyaman Coffee. The results showed that service quality has a positive and significant influence on Nyaman Coffee consumer loyalty, customer satisfaction has a positive and significant influence on consumer loyalty at Nyaman Coffee, and service quality has a positive and significant influence on customer satisfaction at Nyaman Coffee